Manfaat Datawarehouse pada Rumah Sakit ABC - Evaristus Didik M.; M. Awan Wibisono; Sucipto A.; Gusti Agung D. V. (Bina Nusantara University, 2012)
This study is objected to analyze the current system to find the problems being faced by ABC Hospital and propose alternative solutions. Additionally, it aims to generate information needed by the hospital management to design a data warehouse according to the information needs. The research method used is the analysis and design of data warehouse by Kimball and Ross cited by Connolly and Begg, known as Nine-Step Methodology. The result obtained is a data warehouse application with a multidimensional historical data that can assist the hospital management in decision making. Designing data warehouse at ABC Hospital makes enterprise data into concise and can be viewed from several dimensions that help users analyze data for strategic decision quickly and accurately.